Close Observation of Hydraulic Fracturing at EGS Collab Experiment 1: Fracture Trajectory, Microseismic Interpretations, and the Role of Natural Fractures. Issue 7 (16th July 2021) - Fu, Pengcheng; Schoenball, Martin; Ajo‐Franklin, Jonathan B.; Chai, Chengping; Maceira, Monica; Morris, Joseph P.; Wu, Hui; Knox, Hunter; Schwering, Paul C.; White, Mark D.; Burghardt, Jeffrey A.; Strickland, Christopher E.; et al.
Abstract: Despite the wide application of hydraulic fracturing in enhanced geothermal system (EGS) development and unconventional hydrocarbon production, our understanding of the many factors affecting the propagation of hydraulic fractures has relied on circumstantial evidence. This is partly due to the scarcity of direct observations in the subsurface. The EGS Collab project attempts to address these issues in the context of EGS research by performing intermediate‐scale (∼10 m) hydraulic stimulation experiments in a thoroughly characterized and heavily instrumented underground testbed. This paper analyzes the data collected from the first suite of hydraulic fracturing tests in this testbed, consisting of seven stimulation episodes. High‐quality microseismic data delineate five planar features very clearly. Combining fracture‐wellbore intersection observations from distributed temperature sensing (DTS) and visual observations from an open‐hole well, as well as prior in‐situ stress measurements, we conclude with high certainty that the four larger planes were hydraulic fractures. The growth of the hydraulic fractures was temporarily halted by a prominent, open natural fracture in the testbed but they eventually crossed and slightly reoriented under continued stimulation. Mineral‐filled (i.e., healed) natural fractures, though prevalent in the testbed, did not have perceivable effects on hydraulic fracture propagation. The high‐quality, mutually corroborating data sets allowed conclusions to be drawn with high confidence and attests to the advantage of intermediate‐scale experiments in subsurface research. Plain Language Summary: Hydraulic fracturing is a critical process enabling enhanced geothermal system (EGS) development and unconventional hydrocarbon production. Because direct observation in the subsurface is difficult and scarce, our understanding of the many factors affecting the propagation of hydraulic fractures remains vague or unreliable. The EGS Collab project attempts to address these issues in the context of EGS research by performing intermediate‐scale (∼10 m) hydraulic stimulation experiments in a thoroughly characterized and heavily instrumented underground testbed. In this paper, we analyzed the data collected from the first suite of hydraulic fracturing tests in this testbed, consisting of seven stimulation episodes. High‐quality microseismic data delineate five planar features very clearly. Thanks to the many types of data corroborating each other, we conclude with high certainty that the four larger planes were hydraulic fractures. The growth of the hydraulic fractures was temporarily halted by a prominent, open natural fracture in the testbed but they eventually crossed and slightly reoriented under continued stimulation. Mineral‐filled natural fractures, though prevalent in the testbed, did not have perceivable effects on hydraulic fracture propagation. Key Points: A suite of intermediate‐scale hydraulic fracturing experiments in a highly instrumented testbed are presented Microseismicity, distributed temperature, and direct wellbore observations reveal fracture propagation and interaction behaviors An open natural fracture interacts with hydraulic fracture in complex ways while mineral‐filled fractures do not actively participate